Continuous Hemofiltration Reduces Mortality in Severe Acute Pancreatitis: A Meta-Analysis. (29th June 2020) - Guo, Yulin; Cao, Feng; Li, Chen; Yang, Huaxia; Xia, Shaoyou; Li, Fei
Abstract : Background . Severe acute pancreatitis (SAP) is a deadly condition, with a mortality rate ranging from 15% to 30%. Recently, blood purification therapy has been adopted in administrating SAP patients. The present study aimed at evaluating the effect of continuous hemofiltration therapy for SAP. Methods . A systematic search of Cochrane Library, PubMed, and Embase was carried out until October 1 st, 2019. Prospective studies comparing outcomes for SAP patients between continuous hemofiltration and standard therapy were enrolled. Results . Continuous hemofiltration therapy was associated with lower level of PACHE II score (MD = −1.49; 95% CI: −2.69 to −0.29, P = 0.02 ), CRP (MD = −1.56 mg/L; 95% CI: −2.64 to −0.47, P = 0.005 ), Cr (MD = −3.57 umol/L; 95% CI: −5.50 to −1.65, P = 0.003 ), and Bun (MD = −3.63 mmol/L; 95% CI: −6.07 to −1.20, P = 0.003 ) at 72 h after onset of treatment. Continuous hemofiltration therapy was associated with shorter length of abdominal pain relief time (MD = −1.82 hours; 95% CI: −2.93 to −0.71, P = 0.001 ), lower surgery rate (OR = 0.15; 95% CI: 0.03 to 0.78, P = 0.02 ), and mortality rate (OR = 0.54; 95% CI: 0.37 to 0.77, P = 0.0007 ). Conclusions . continuous hemofiltration therapy could effectively alleviate SAP as early as 72 hours after onset of treatment, lowering the level of Bun, Cr, CRP, and APACHE II scores. Continuous hemofiltration therapy could confer SAP patients with lower mortality rates.